Magnetic nanosorbents of γ-polyglutamic acid for removing a β-blocker from water - Campos, Valquíria [UNESP]; Marques, Diego Gouveia [UNESP]; Nogueira, João; Amorim, Carlos O.; Daniel-da-Silva, Ana Luísa; Trindade, Tito (Elsevier, 2023)
Metoprolol is known as one of the most frequently used β-blockers to treat hypertension, however due to its widespread use and resistance to hydrolysis, concerning amounts of this medicine are found in surface waters, causing negative impacts on the environment and human health. To date, very few water treatment plants remove metoprolol due to the ineffectiveness of conventional procedures, thus indicating the need for more efficient water treatments for eliminating traces of this drug from aqueous wastes. A promising strategy is the development of magnetic assisted sorbents with a high surface area and adequate chemical modification aimed at the target pollutant, offering the possibility of total removal from water supplies and thus limiting potential environmental impacts. In this context, the purpose of this work was to investigate the application of magnetic Fe3O4 nanoparticles coated with silica and γ-polyglutamic acid to capture metoprolol dissolved in water. The synthesized sorbents consisted of magnetite nanoparticles with an average size of 55.8 nm, coated with a layer of amorphous silica covalently bound to γ-polyglutamic acid, thus exposing carboxylate surface active sites, which favor electrostatic interactions with metoprolol. As the γ-polyglutamic acid sources, two types of materials with distinct amounts in the biopolymer (30% and 92%) have been investigated. The adsorption of metoprolol by the nanosorbents γ-PGA/Fe3O4 was evaluated by means of adsorption isotherms and theoretical adsorption models. Freundlich and Langmuir models provide an accurate description of the isotherm, and the compound's maximum adsorption capacity was 571.6 mg g−1. Noteworthy, the magnetic nanosorbents prepared using γ-polyglutamic acid 30% and 92% have shown comparable performances, which makes this process also economically attractive considering that a low-cost raw material can be used.
Keywords: Magnetic nanoparticles; Metoprolol; Water treatment; γ-polyglutamic acid